Rapid Screening of Colorado Potato Beetle Resistance Derived from Solanum okadae - Hanna J. McCoy; Sean Fenstemaker; Pamela MacKinley; Jess Vickruck; John Bamberg; Larry A. Calhoun; Helen H. Tai (American Journal of Potato Research, 2024)
Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say) is a major insect pest of potato and development of resistant varieties is part of a strategy for management. Wild relatives of potato are resources for genetic improvement through breeding. Interspecies crosses to introgress CPB resistance will be facilitated with rapid and inexpensive selection methods. Solanum okadae is a novel source of feeding deterrence against the beetle and was associated with production of a naturally occurring leaf-specific lactone-containing metabolite in the foliage. The Baljet assay has been used for decades in pharmaceuticals for rapid screening of lactone-containing compounds. A modified Baljet assay was developed for potato foliar tissue to rapidly screen for lactone-containing compounds in plants from the field, greenhouse, and laboratory. Herein we report the screening of potato foliage for CPB resistance with a Baljet assay validated by CPB larval feeding studies. Foliage from wild accessions of S. okadae were tested using the Baljet assay and results showed that production of the leaf-specific lactones has a large range of variation in the species. In addition, tubers tested using the Baljet assay had negligible levels of lactone-containing metabolites, confirming leaf-specific production of lactones. This inexpensive method using leaf disk screening will allow potato breeders to quickly select for potential CPB resistant germplasms and advance the breeding of sustainable crops.

Colorado Potato Beetle Resistance in Solanum oplocense X Solanum tuberosum Intercross Hybrids and Metabolite Markers for Selection - Helen H. Tai; Kraig Worrall; David De Koeyer; Yvan Pelletier; George C. C. Tai; Larry Calhoun (American Journal of Potato Research, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The MCIC Collection: A Shared Repository of Multi-Modal, Multi-Site Brain Image Data from a Clinical Investigation of Schizophrenia - Randy L. Gollub; Jody M. Shoemaker; Margaret D. King; Tonya White; Stefan Ehrlich; Scott R. Sponheim; Vincent P. Clark; Jessica A. Turner; Bryon A. Mueller; Vince Magnotta; Daniel O’Leary; Beng C. Ho; et al. (Neuroinformatics, 2013)